202k views
0 votes
Find all solutions to


\sqrt[3]{15x-1} + \sqrt[3]{13x+1} =4\sqrt[3]{x}
Enter all the separated, seperated by commas.

User Slimu
by
5.4k points

1 Answer

3 votes

Answer:

x= 0 ,
(1)/(14) ,
(-1)/(12)

Explanation:

Given, equation is
\sqrt[3]{15x-1} +
\sqrt[3]{13x+1} =
4\sqrt[3]{x}. →→→ (1)

Now, by cubing the equation on both sides, we get

(
\sqrt[3]{15x-1} +
\sqrt[3]{13x+1} )³ = (
4\sqrt[3]{x}

⇒ (15x-1) + (13x+1) + 3×
\sqrt[3]{15x-1}×
\sqrt[3]{13x+1} (
\sqrt[3]{15x-1} +
\sqrt[3]{13x+1}
) = 64 x.

⇒ 28x + 3×
\sqrt[3]{15x-1}×
\sqrt[3]{13x+1} (
4\sqrt[3]{x}
) = 64x.

(since from (1),
\sqrt[3]{15x-1} +
\sqrt[3]{13x+1} =
4\sqrt[3]{x})

⇒ 12×
\sqrt[3]{15x-1}×
\sqrt[3]{13x+1} (
\sqrt[3]{x})= 36x.

⇒ 3x =
\sqrt[3]{(15x-1)(13+1)(x)}.

Now, once again cubing on both sides, we get

(3x)³ = (
\sqrt[3]{(15x-1)(13+1)(x)})³.

⇒ 27x³ = (15x-1)(13x+1)(x).

⇒ 27x³ = 195x³ + 2x² - x

⇒ 168x³ + 2x² - x = 0

x(168x² + 2x -1) = 0

⇒ by, solving the equation we get ,

x = 0 ; x =
(1)/(14) ; x =
(-1)/(12)

therefore, solution is x= 0 ,
(1)/(14) ,
(-1)/(12)

User Bowen Liu
by
6.1k points